Tanggung Jawab Hukum Perawat yang Melakukan Tindakan Medis di Luar Kewenangan Berdasarkan UU No. 38 Tahun 2014 Tentang Keperawatan - Aisah Berlianti; Djoko Purwanto (Universitas Medan Area, 2023)
The purpose of this research is to determine the legal responsibility of nurses who carry out medical procedures outside their authority based on Law Number 38 of 2014 concerning Nursing and the Responsibility of health workers who carry out medical procedures outside their authority based on Law Number 36 of 2014 concerning health workers. The type of research used is normative juridical research which refers to the use of conceptual and statutory analysis, where the material comes from primary legal materials, secondary legal materials and tertiary legal materials. The results found that nurses should only carry out nursing care actions in accordance with the Nursing Law and in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 26 of 2019 concerning Implementing Regulations of the Nursing Law which requires nurses to carry out their duties by being equipped with a nurse registration certificate and a permit. Nurse practice Nurses who carry out medical procedures without authority will incur criminal, civil and administrative liability. With actions taken by nurses without authority, this can result in losses for many parties, both material and immaterial losses and will worsen the good image of health workers, especially nurses.